Relationship between multiple simple hepatic cysts and vesicular lithiasis - Mendoza Rojas, Hubert James (2018)
Objective: To know if there is a relationship between multiple simple hepatic cysts and vesicular lithiasis. Materials and methods: An observational, retrospective and cross-sectional study was performed with a non-probability convenience (accidental) sampling. The sample size consisted of 50 patients diagnosed with simple hepatic cysts by ultrasound. Results: The most frequent age group was between 61 and 70 years (32 %), and the female gender was the most common one (92 %). The simple hepatic cysts had a mean volume of 87.58 cc, with a minimum volume of 0.16 cc and a maximum of 1255 cc. Multiple cysts accounted for 48 % of all cysts. Pearson’s linear correlation coefficient for variables age and cyst volume was 0.035. Fifty-five point four percent (55.4 %) of the cysts were located in the right lobe, mostly on segment II (17.3 %). Fifty-six percent (56 %) of simple hepatic cysts were found in normal livers, followed by 36 % in livers with steatosis. Eighty- three point seven eight percent (83.78 %) did not show vesicular lithiasis. No dilation of bile ducts was found in 100 % of the cases. There was no relationship between multiple simple hepatic cysts and lithiasis (0.828) (p < 0.05). Conclusions: There was no evidence of a relationship between multiple simple hepatic cysts and vesicular lithiasis.